2020
DOI: 10.1371/journal.pone.0226238
|View full text |Cite
|
Sign up to set email alerts
|

MLST-based genetic relatedness of Campylobacter jejuni isolated from chickens and humans in Poland

Abstract: Campylobacter jejuni infection is one of the most frequently reported foodborne bacterial diseases worldwide. The main transmission route of these microorganisms to humans is consumption of contaminated food, especially of chicken origin. The aim of this study was to analyze the genetic relatedness of C. jejuni from chicken sources (feces, carcasses, and meat) and from humans with diarrhea as well as to subtype the isolates to gain better insight into their population structure present in Poland. C. jejuni wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…Meanwhile, consistent with our finding, ST-50 and ST-19 (CC21) and ST-257 were mostly related to human campylobacteriosis cases [ 36 38 ]. However, isolates from other sources (fresh whole retail chicken, raw milk and environmental water) also presented CC21 as dominant CCs [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, consistent with our finding, ST-50 and ST-19 (CC21) and ST-257 were mostly related to human campylobacteriosis cases [ 36 38 ]. However, isolates from other sources (fresh whole retail chicken, raw milk and environmental water) also presented CC21 as dominant CCs [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Within CC21, ST-50 was the dominant ST in our clinical samples, although not all of previous studies reported ST-50 as the dominant sequence type [34,35]. Meanwhile, consistent with our finding, ST-50 and ST-19 (CC21) and ST-257 were mostly related to human campylobacteriosis cases [36][37][38]. However, isolates from other sources (fresh whole retail chicken, raw milk and environmental water) also presented CC21 as dominant CCs [39,40].…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, consistent with our nding, ST-50 and ST-19 (CC21) and ST-257 were mostly related to human campylobacteriosis cases [36][37][38]. However, isolates from other sources (fresh whole retail chicken, raw milk and environmental water) also presented CC21 as dominant CCs [39,40].…”
Section: Discussionsupporting
confidence: 83%
“…Globally, CC-45 has been found in various hosts, including poultry, cattle, dogs, wild birds, penguins, and it was also isolated from environmental samples ( Cody et al, 2012 ; Shin et al, 2013 ), while CC-607 is largely associated with chicken and humans as reported from the United Kingdom, France, Canada, Thailand, and Uruguay ( Cody et al, 2012 ; Duarte et al, 2014 ; Guyard-Nicodème et al, 2015 ). ST-45 and ST-50, predominant in Korea, are also common in C. jejuni from chickens in Europe ( Wieczorek et al, 2020b ). In 2019, ST-21, ST-50, and ST-137 have been isolated from wild ducks, indicating their widespread distribution ( Wei et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%